Penerapan Tri Hita Karana terhadap Kawasan Agrowisata Buyan dan Tamblingan di Desa Pancasari, Kecamatan Sukasada, Kabupaten Buleleng - I K. SUKERADA; I N. SUTJIPTA; I G. SETIAWAN AP (Universitas Udayana, 2013)
Agro-tour is one of the alternative developments of tour destination in Indonesia, especially in Bali which has high number of devotees. The agro-tour area in Buyan/Tamblingan is one of the agro-tour areas which is developed intensively in Bali. The value of this agro-tour will be higher if it is focused on its management. The relevant basis used to manage and keep the viability of this agro-tour is named Tri Hita Karana. Besides as being a guidance for managing, the aspects of Tri Hita Karana is also considered as tourism value which is divided into three aspects, namely parhyangan, pawongan, and palemahan. Based on this situation, this study aimed at understanding the effect of Tri Hita Karana implementation simultaneously or partially toward the agro-tour area of Buyan/Tamblingan. The population of this study was the community of Pancasari village with 1.100 KK. The sample of this study was 110 people chosen by using simple random sampling technique. The data was analyzed by using multiple regressions analysis, correlation analysis, determination analysis, F-test analysis, and standardized coefficient beta through SPP 17.0 program. The result of this study shows that the implementation of Tri Hita Karana consisting of parhyangan, pawongan, and palemahan simultaneously influences positively and significantly toward the agro-tour area of Buyan/Tamblingan with Fcounted of 86.659 and significance degree of 0.000 which is beneath from 5%. Partially, the aspect of parhyangan has positive and significant influence toward the agro-tour area of Buyan/Tamblingan with tcounted > ttabel (3.708 > 1.659) with probability value (? = 5%) is 0.000 which is beneath from 0.05. The aspect of pawongan has positive and significant influence toward agro-tour area of Buyan/Tamblingan with tcounted > ttabel (2.604 > 1.659) with probability value (? = 5%) is 0.011 which is beneath from 0.05. The aspect of palemahan has positive and significant influence toward agro-tour area of Buyan/Tamblingan with tcounted > ttabel (4.519 > 1.659) with probability value (? = 5%) is 0.000 which is beneath from 0.05. Thus, the most influent variable is palemahan which has the highest standardized coefficient beta of 0.389 with the highest determination influence of 38.9%.Based on the result of this study, it is expected for the tourism manager and community appliance that the management of agro-tour area of Buyan/Tamblingan as a tour destination pays attention on the aspects of Tri Hita Karana as a philosophy in keeping, protecting, employing, and developing this agro-tour area since these aspects of Tri Hita Karana is proven to have significant effect simultaneously and partially.